The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/rem.21511
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Zero‐Valent Iron (ZVI) Technology to Promote DDT and Dieldrin Degradation at Point Pelee National Park

Abstract: Point Pelee National Park (PPNP) is highly contaminated with dichlorodiphenyltrichloroethane (DDT) and dieldrin due to the historical use of these two persistent organochlorine pesticides. Zero‐valent iron (ZVI) technology with and without amendments has been successfully used in the past to promote organochlorine pesticides degradation in several locations in North America and Europe. In this study, the use of two commercially available ZVI products, DARAMEND® and EHC®, to promote DDT and dieldrin degradation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Indeed, Comfort et al (2001) and Shea et al (2004) observed a decrease in metolachlor concentration of 70 and 98% in the soil directly after 90 days with ZVI, ZVI + AA or ZVI + AS. In contrast, the results of Dahmer et al (2017) showing that the in situ application of DARAMEND ® (commercial product composed of 40-50% ZVI and 50-60% Organic Matter) at 2% (w/w) had no effect on Dieldrin and DDT concentrations, and the same observations were reported by Ševců et al (2017) indicating that ZVI was ineffective in treating PCBs in the soil The physicochemical properties of the contaminants could explain these differences, the accessibilities to the reduction of chlorine atoms must depend on the molecules. Indeed, Yang et al (2010) showed a slight effect of ZVI to degrade some DDx and HCx, only β-HCH, DDT and DDE were affected, as well as the capacity of ZVI to degrade Dieldrin in soil seems to be limited.…”
Section: Zvi Degradationmentioning
confidence: 78%
“…Indeed, Comfort et al (2001) and Shea et al (2004) observed a decrease in metolachlor concentration of 70 and 98% in the soil directly after 90 days with ZVI, ZVI + AA or ZVI + AS. In contrast, the results of Dahmer et al (2017) showing that the in situ application of DARAMEND ® (commercial product composed of 40-50% ZVI and 50-60% Organic Matter) at 2% (w/w) had no effect on Dieldrin and DDT concentrations, and the same observations were reported by Ševců et al (2017) indicating that ZVI was ineffective in treating PCBs in the soil The physicochemical properties of the contaminants could explain these differences, the accessibilities to the reduction of chlorine atoms must depend on the molecules. Indeed, Yang et al (2010) showed a slight effect of ZVI to degrade some DDx and HCx, only β-HCH, DDT and DDE were affected, as well as the capacity of ZVI to degrade Dieldrin in soil seems to be limited.…”
Section: Zvi Degradationmentioning
confidence: 78%